Content Analysis of English Textbook for Eleventh Graders Based on Merdeka Curriculum at SMA Negeri 1 Pracimantoro - Fatimah, Utami Nur; Budiharso, Teguh; Giyoto (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study analyzes the